2
$\begingroup$

Let $n \in (1,+\infty)$, I've shown that the function $$ I(n)=\int_{0}^{+\infty}\arctan\left(\frac{1}{x^n}\right)\,\mathrm{d}x $$ is defined on $(1,+\infty)$ and that it can be expressed by $$ I(n)=\frac{1}{n}\int_{0}^{+\infty}\frac{\arctan\left(x\right)}{x^{(n+1)/n}}\,\mathrm{d}x $$ I wanted to know if there was a way to compute this kind of integral. I know that $$ I\left(2\right)=\frac{\pi}{\sqrt{2}}, \quad I\left(3\right)=\frac{\pi}{\sqrt{3}}. $$ Despite that I did not manage to prove it, it was starting well to find a beautiful formula however it becomes difficult to compute for odd integer value of $n$ and gives strange value for even integer value.

Any help?

$\endgroup$
4
  • $\begingroup$ Since $x$ is the variable of integration and $I$ is a definite integral, $I$ can't be a function of $x$. You're integrating starting at $0$, yet you've restricted $x$ to $(1,\infty).$ $\endgroup$ – B. Goddard Feb 22 '18 at 12:17
  • $\begingroup$ @B.Goddard Sorry, i've made a mistake $\endgroup$ – Atmos Feb 22 '18 at 12:19
  • $\begingroup$ I've edited this question in order to remove the \displaystyle in the title. For further info, you may consult Why no use displaystyle in titles on Math.Meta.SE. $\endgroup$ – GNUSupporter 8964民主女神 地下教會 Feb 22 '18 at 12:19
  • $\begingroup$ It looks like $I(n)=\dfrac{\pi}{2\cos(\pi/2n)}$. $\endgroup$ – user436658 Feb 22 '18 at 13:09
5
$\begingroup$

Another solution is to invoke the formula

$$ \forall 0 < m < n \ : \quad \int_{0}^{\infty} \frac{x^{m-1}}{1+x^n} \, dx = \frac{\pi}{n}\csc\left(\frac{\pi m}{n}\right) \tag{1} $$

whose proof can be found here. Indeed,

\begin{align*} I(n) &= \int_{0}^{\infty} \frac{\arctan(x^n)}{x^2} \, dx \tag{$x\mapsto 1/x$} \\ &= \left[-\frac{1}{x}\arctan(x^n) \right]_{x=0}^{x=\infty} + \int_{0}^{\infty} \frac{nx^{n-2}}{1 + x^{2n}} \, dx \tag{IbP} \\ &= n \cdot \frac{\pi}{2n}\csc\left(\frac{\pi (n-1)}{2n}\right) \tag{by (1)} \\ &= \frac{\pi}{2}\sec\left(\frac{\pi}{2n}\right). \end{align*}

$\endgroup$
4
$\begingroup$

It is:

$$I(n)=\color{red}{\int_0^{\infty } \tan ^{-1}\left(\frac{1}{x^n}\right) \, dx}=\\\int_0^{\infty } \mathcal{L}_a^{-1}\left[\tan ^{-1}\left(\frac{a}{x^n}\right)\right](s) \, dx=\\\mathcal{L}_s\left[\int_0^{\infty } \left(\frac{\pi \delta (s)}{2}-\frac{\sin \left(s x^n\right)}{s}\right) \, dx\right](1)=\\\mathcal{L}_s\left[-s^{-1-\frac{1}{n}} \Gamma \left(1+\frac{1}{n}\right) \sin \left(\frac{\pi }{2 n}\right)\right](1)=\\-\Gamma \left(1+\frac{1}{n}\right) \Gamma \left(-\frac{1}{n}\right) \sin \left(\frac{\pi }{2 n}\right)=\\\color{red}{\frac{1}{2} \pi \sec \left(\frac{\pi }{2 n}\right)}$$

$\endgroup$
4
$\begingroup$

Here is yet another approach that uses Feynman's trick of differentiating under the integral sign.

We begin by enforcing a substitution of $x \mapsto x^{1/n}$. This gives $$\int_0^\infty \tan^{-1} \left (\frac{1}{x^n} \right ) \, dx = \frac{1}{n} \int_0^\infty \frac{\tan^{-1} x}{x^{1 + \frac{1}{n}}} \, dx, \quad n > 1.$$ Now let $$I(a) = \frac{1}{n} \int_0^\infty \frac{\tan^{-1} (ax)}{x^{1 + \frac{1}{n}}} \, dx, \quad a > 0.$$ Note that $I(0) = 0$ and we are required to find the value of $I(1)$.

Differentiating with respect to the parameter $a$ yields $$I'(a) = \frac{1}{n} \int_0^\infty \frac{x^{-1/n}}{1 + a^2 x^2} \, dx,$$ or $$I'(a) = \frac{a^{\frac{1}{n} - 1}}{2n} \int_0^\infty \frac{t^{-\frac{1}{2n}-\frac{1}{2}}}{1 + t} \, dt,$$ after a substitution of $x \mapsto \sqrt{t}/a$ has been enforced. The integral appearing above can be expressed in terms of Euler's Beta function $\text{B}(x,y)$. Here \begin{align*} I'(a) &= \frac{a^{\frac{1}{n} - 1}}{2n} \int_0^\infty \frac{t^{(\frac{1}{2} - \frac{1}{2n}) - 1}}{(1 + t)^{(\frac{1}{2}-\frac{1}{2n}) + (\frac{1}{2} + \frac{1}{2n})}} \, dt\\ &= \frac{a^{\frac{1}{n}-1}}{2n} \text{B} \left (\frac{1}{2} - \frac{1}{2n}, \frac{1}{2} + \frac{1}{2n} \right )\\ &= \frac{a^{\frac{1}{n} - 1}}{2n} \Gamma \left (\frac{1}{2} - \frac{1}{2n} \right ) \Gamma \left (\frac{1}{2} + \frac{1}{2n} \right )\\ &= \frac{a^{\frac{1}{n} - 1}}{2n} \Gamma \left [1 - \left (\frac{1}{2} + \frac{1}{2n} \right ) \right ] \Gamma \left (\frac{1}{2} + \frac{1}{2n} \right )\\ &= \frac{a^{\frac{1}{n} - 1}}{2n} \frac{\pi}{\sin \pi \left (\frac{1}{2} + \frac{1}{2n} \right )} \tag1\\ &= \frac{\pi}{2n} \sec \left (\frac{\pi}{2n} \right ) a^{\frac{1}{n} - 1}, \end{align*} where in (1) Euler's reflection formula has been used.

So on integrating up with respect to the parameter $a$ we have \begin{align*} I(1) &= \int_0^1 I'(a) \, da = \frac{\pi}{2n} \sec \left (\frac{\pi}{2n} \right ) \int_0^1 a^{\frac{1}{n} - 1} \, da = \frac{\pi}{2} \sec \left (\frac{\pi}{2n} \right ) \Big{[} a^{\frac{1}{n}} \Big{]}_0^1 \end{align*} giving $$\int_0^\infty \tan^{-1} \left (\frac{1}{x^n} \right ) \, dx = \frac{\pi}{2} \sec \left (\frac{\pi}{2n} \right ),$$ as expected.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.